[Translated article] Postoperative Wound Care in Dermatologic Surgery: Update And Narrative Review - A. Sanchez-Puigdollers; A. Toll; D. Morgado-Carrasco (Actas Dermo-Sifiliográficas)
Dermatologic surgery is associated with a very low risk of complications. There is no widely accepted, evidence-based protocol with recommendations for postoperative wound care after dermatologic surgery. In this narrative review, we will be discussing the evidence on surgical wound care products and procedures. Overall, we found relatively few studies and, in many cases, a lack of statistically significant differences, possibly because of the low rate of complications. We’ll be discussing the evidence on when we should initiate wound care procedures and their frequency, the type of ointment and antiseptics that should be applied, and the type of dressings that should be used. Despite the very few studies available on postoperative wound care following dermatologic surgery, there is sufficient evidence as to not recommend the use of prophylactic topical antibiotics. We also analyze the currently available evidence on surgical wound care in special situations, such as management of skin grafts, partial skin graft donor sites, xenografts/biomembranes, and surgical wounds to the legs. Resumen: La cirugía dermatológica asocia un riesgo de complicaciones muy bajo. No existe un protocolo universalmente aceptado sobre las recomendaciones de curas poscirugía dermatológica. En esta revisión narrativa, discutimos la evidencia sobre productos y procedimientos para el cuidado de la herida quirúrgica. En general, encontramos escasos estudios y en muchas ocasiones, falta de diferencias estadísticamente significativas, posiblemente dada la baja tasa de complicaciones. Discutimos la evidencia sobre cuándo iniciar las curas y su frecuencia, el tipo de ungüento a aplicar, los antisépticos y el tipo de apósito a utilizar. Pese a los escasos estudios sobre las curas tras cirugía dermatológica, existe evidencia suficiente para desaconsejar la utilización de antibióticos tópicos profilácticos. También analizamos la evidencia publicada sobre el cuidado de la herida quirúrgica en situaciones especiales, como son los injertos cutáneos, las zonas dadoras de injertos cutáneos de espesor parcial, los xenoinjertos/biomembranas y las heridas quirúrgicas en las piernas.